BSI COMPETITIVE STRATEGY AFFECT PURCHASING DECISIONS OF CONVENTIONAL BANK CUSTOMERS IN INDONESIA - Ahmad Syarief Iskandar; Muzayyanah Jabani; Muh. Shadri Kahar Muang (International Journal of Artificial Intelligence Research, 2022)
This study tries to explain and analyze what strategies Bank BSI has in its competitive process, and how it affects the purchasing decisions of conventional bank customers. The study of competitive strategy at BSI bank is very strategic to discuss because it is a study of contemporary issues and is urgently needed at a time when Islamic banking institutions are becoming mainstream for customers in Indonesia. This research is reveal that Â The cost leadership variable has a positive and significant effect on purchasing decisions at Bank BSI. Variable differentiation has a significant positive effect on purchasing decisions at Bank BSI, which means that the better differentiation at Bank BSI, it will not improve purchasing decisions. customer. variable focus has a positive and significant effect on purchasing decisions on BSI bank products, which means the better the focus at BSI Bank, the better purchasing decisions will be. The limitation of this research is that it has not conducted experimental research related to consumer psychology. In-depth research on consumers needs to be done qualitatively with a phenomenological approach. In addition, the population space is very small so that the sampling technique only makes cluster sampling limited to one area so that it is possible to choose a larger cluster sampling area.